2014
DOI: 10.1016/j.ypmed.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sedentary time and cardiometabolic risk among Canadian adults

Abstract: These findings in a large representative sample of Canadian adults indicate that breaking up sedentary time may be particularly important for cardiometabolic health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
4
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 23 publications
9
141
4
5
Order By: Relevance
“…Our analyses indicated that EVA derivatives reflecting the temporal sitting pattern (ie, brief bursts, and moderate and prolonged periods) were not associated with LBP intensity. This stands in contrast to studies arguing that breaks from prolonged sitting are beneficial for health outcomes (49)(50)(51). However, breaks from sitting may increase the exposure to other risk factors for LBP, such as awkward working postures (6,52).…”
Section: Discussionmentioning
confidence: 70%
“…Our analyses indicated that EVA derivatives reflecting the temporal sitting pattern (ie, brief bursts, and moderate and prolonged periods) were not associated with LBP intensity. This stands in contrast to studies arguing that breaks from prolonged sitting are beneficial for health outcomes (49)(50)(51). However, breaks from sitting may increase the exposure to other risk factors for LBP, such as awkward working postures (6,52).…”
Section: Discussionmentioning
confidence: 70%
“…However, an increase in SB breaks was not associated with a decline in LDL-C. Conversely, a 0.21 mmol l −1 (CI 95 % −0.38-0.04) decline in LDL-C was associated with an hourly increase in MVPA (Carson et al 2014). As a result, reducing SB by increasing LIPA appears to be partly beneficial in the management of cholesterol and LPL.…”
Section: Sedentary Behaviour and Physical Activity: Impact On Glucosementioning
confidence: 84%
“…This move towards a more consistent thinking with regards to the modern conceptualisation of sedentariness is born out of recent findings demonstrating that SB holds deleterious consequences for health independently of any beneficial effects of physical activity engagement [4][5][6][7][8][9][10][11]. In particular, there is evidence that implicates SB as a precursor of heightened systemic inflammation in both healthy and clinical populations, irrespective of levels of the anti-inflammatory effect of physical activity [8][9][10][11].…”
Section: Sedentary Behaviour: Definition and Health Relevancementioning
confidence: 99%
“…In particular, there is evidence that implicates SB as a precursor of heightened systemic inflammation in both healthy and clinical populations, irrespective of levels of the anti-inflammatory effect of physical activity [8][9][10][11]. Indeed, there now exists a considerable amount of evidence demonstrating SB to be an independent risk factor for cardiovascular disease, the metabolic syndrome, sarcopenia and Type 2 diabetes, all of which have chronic systemic inflammation in common [9,10,[12][13][14][15][16]. These independent health effects may result from differences in the acute and chronic physiological responses to sedentary behaviour vs. physical activity engagement [17].…”
Section: Sedentary Behaviour: Definition and Health Relevancementioning
confidence: 99%
See 1 more Smart Citation